Pioneer Rocketry Proceedings Report 2019 - Bohlman, Elizabeth (Proceedings of the Wisconsin Space Conference, 2020)
The Wisconsin Space Grant Consortium hosts the annual Collegiate Rocket Launch Competition every year. The goal of the competition this year was to design and build a rocket to fly to between 700 and 1000 ft and deploy an autonomous ground excursion vehicle upon landing. The rocket, Istanbul, used a CTI J357 motor to lift it to an apogee of 896 ft, and successfully deployed the ground excursion module after landing. On the second flight attempt, Istanbul achieved an apogee of 742 ft, much closer to the predicted apogee of 750 ft. Unfortunately, during this second flight, Istanbul landed in water, disqualifying the flight. Pioneer Rocketry is very proud to have placed first in this competition, winning the title of Mission Grand Champion.